PENGARUH VARIASI DAYA LASER CO2 TERHADAP PERUBAHAN WARNA PERMUKAAN DAN PREFERENSI KONSUMEN PADA KAYU CEMPAKA (Michelia champaca) - Suri, Intan Fajar; Nugraha, Muhammad Dimaz; Al Qorny, Faiz; Febryano, Indra Gumay; Hidayat, Wahyu (Jurnal Nusa Sylva, 2025)
Laser technology has become one of the main innovations in material delivery, especially in the wood industry for cutting and engraving purposes. One of the advantages of this technology is the ability to produce precise and aesthetic patterns on the wood surface. However, each type of wood has unique characteristics to the heat treatment of the laser beam, so further research is needed to understand the specific response of each type of wood. This study aims to trigger the effect of variations in CO₂ laser power on changes in the surface color of cempaka wood (Michelia champaca) and to identify consumer preferences for the color results. The study was conducted at the Forest Products Technology Laboratory, University of Lampung, using three variations of laser power: 2.5 watts, 5 watts, and 7.5 watts, with each treatment repeated three times. The surface color was described using a CIE-Lab system-based colorimeter (parameters L*, a*, and b*) before and after engraving. In addition, a consumer preference survey was conducted boldly involving 100 students from the University of Lampung to assess the visualization of the engraving results. The results showed that higher laser power (7.5 watts) produced darker and more contrasting wood colors, with a decrease in L* values and an increase in a* and b* values. Most respondents preferred the results of engraving using 7.5 watts of power because it produced darker colors and was considered more aesthetic and gave sharper results.